Spontaneous Regression of Meningiomas: Literature Review and Case Report - Özen, Ali; Güngör, Abuzer; Türe, Uğur (Asian Journal of Neurosurgery, 2025)
Meningiomas are one of the most common primary tumors of the central nervous system, and surgical excision is the gold standard treatment for symptomatic patients. But there is no common algorithm for treatment in asymptomatic patients. Many studies have investigated the natural course of incidental meningiomas. Spontaneous regression refers to the shrinkage of a tumor without any intervention or treatment. Current data on spontaneous regression of meningiomas consists only of case reports. In this article, we present the case of a patient with an incidental meningioma that spontaneously regressed during follow-up and include a review of the literature.
Keywords: asymptomatic meningioma; incidental meningioma; regression; shrinkage; spontaneous